Comparative evaluation of host plants for ericulture with special reference to Musiri, Tamil Nadu, India - Gokulakrishnaa , R K; Devasri , M; Charu , H S; Barjana , B A; Bhuvana , L R; Deepika , D; Jothika , P (Plant Science Today, 2025)
The versatile eri silkworm, a fully domesticated species, can thrive on a variety of plants, including castor and tapioca, making it a year-round producer. However, its production is sensitive to both climate and the nutritional value of its host plants. This study aimed to determine the influence of castor and tapioca, two widely cultivated host plants, on the growth and development of eri silkworms in Musiri, Trichy District, Tamil Nadu, India. Biochemical analysis of selected cultivars was conducted using standard methods outlined by the Association of Official Analytical Chemists. Silkworm rearing and morphometric analysis were carried out following the standard protocol. The nutrient composition of pupae was analysed at Tamil Nadu Veterinary and Animal Science University (TANUVAS), Namakkal, Tamil Nadu, India, to assess their potential as a valuable resource for future research. The study found that castor leaves contained significantly higher levels of nutrients, including nitrogen, phosphorus, potassium, crude protein, total minerals and total carbohydrates, while exhibiting lower levels of anti-nutrients, particularly total tannins, compared to tapioca leaves. This superior nutritional profile led to significantly better performance of silkworms reared on castor, as evidenced by various economic parameters and morphometric analysis. The higher nutrient content of castor-reared pupae was also confirmed through proximate composition analysis. Based on the findings of this study, it is highly recommended that farmers integrate ericulture with castor or tapioca cultivation. By adopting optimal leaf removal practices, farmers can significantly increase their income from both silk production and crop yields. Additionally, this integrated approach can contribute to sustainable agricultural practices.